The effectiveness of constructive learning strategy in teaching social studies and citizenship on developing historical thinking skills for middle school students in the Holy Capital - Ameen, Sahar Abdulwahab; Al-Ahdal, Asma Zain (Journal of Educational and Psychological Sciences, 2021)
The research examined the effectiveness of the constructive learning strategy in teaching social studies and citizenship on developing historical thinking skills of second-grade intermediate students. The researcher used a semi-experimental approach, and the sample consisted of (50) students from the 13TH Intermediate School in Makkah (Saudi Arabia) distributed randomly to: (25) control group, and (25) experimental group. The experimental group was taught using the constructive learning strategy, while the control group was taught in the usual way. To achieve the research goal, a teacher’s guide was prepared to teach the “Umayyad State Unit” using the constructive learning strategy, and a list of historical thinking skills appropriate for the age stage, and an achievement test in the Umayyad State Unit. Results: There were statistically significant differences at the level of 0.05 between the mean scores of the experimental group students in the pre-post measurements of the historical thinking skills test in favor of the post measurement, - existence of statistically significant differences at the level of 0.05 between the mean scores of the students of the control and experimental groups in the post-measurement of the historical thinking skills test favoring the experimental group. Recommendations: The researcher suggested a number of recommendations such as: Using the constructive learning strategy in teaching social studies and citizenship to develop historical thinking skills at all school levels, - creating an educational and classroom environment that supports the constructive learning strategy in teaching social studies and citizenship to develop historical thinking skills, making use of educational platforms in distance teaching using a constructive learning strategy, - provide opportunities to train teachers to implement strategies and models of constructive learning.